Activism and protest - Healey, Justin (Issues in society (Balmain, N.S.W.), 2020)
In a free society such as Australia, the right to peaceful protest is a long-practised feature of our democracy. The nightly news frequently broadcasts images of activists rallying for social change on diverse issues ranging from animal rights to coal mines, gay marriage, religious freedom and antiimmigration views. Social change movements are increasingly championed online through social media and e-petitions as well as on the streets, placing pressure on political leaders and raising the public profile of a range of causes. Anti-protest laws, expanded police powers, well-resourced activism campaigns during elections, chaotic vegan protests and mass climate change action by school students, have all directed a spotlight on the principles of protest and the role of activist groups in organising resistance and raising awareness of controversial causes. This title examines protest movements, rights and protections, and explores how activism can influence public opinion and hold governments and business to account. Is the current climate of protest in Australia growing hotter for social change, reflecting the civil unrest seen in many other parts of the world? Is there a rising tide of activism that is shifting power to the people?